Pollinator‐Mediated Interactions Affect Patterns of Selection on Floral Traits of Co‐Flowering Plants - Yan Ma; Xiaoli Wang; Yizhi Qiu; Zhigang Zhao (Ecology and Evolution)
ABSTRACT The importance of species interactions in shaping the evolution of ecological communities is well established, as they can significantly alter biotic selection. Pollinator‐mediated plant–plant interactions on plant reproductive performance can vary from facilitation to competition. Although the richness and density of co‐flowering species influence patterns of selection, the role of key species in an ecological community remains unclear. We experimentally removed flowers of a dominant flowering species, Ranunculus tanguticus, in an alpine meadow on the Qinghai‐Tibet Plateau, and examined how this dominant affected fitness components and phenotypic selection on floral traits of five neighboring species via stigmatic pollen load. R. tanguticus had a positive effect on the pollen receipt of two plant species, A. obtusiloba and A. souliei. Correspondingly, flower attractive traits (flower height and size) rather than the mechanical‐fit trait (stigma position) of both plants were subjected to significant net selection (i.e., selection differential) when R. tanguticus flowers were removed from the community. Moreover, two species (P. fragarioides and T. lanceolata) among the remaining three flowering plants, which exhibited neutral effects on pollen load when R. tanguticus was removed, experienced stronger phenotypic selection on flower size due to increased opportunities for selection. These findings show that the loss of the flowering‐dominant R. tanguticus in alpine communities can intensify selection on floral attractive traits of co‐flowering plants, independent of the nature of interspecific interactions. This highlights the evolutionary consequences of changes in community composition and biotic interactions in response to environmental shifts.